Optical Fiber Interferometric Sensors New Production Methodologies and Novel Applications - André, Paulo; Alberto, Nélia J.; de Fátima Domingues, Maria (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The contributions presented in this book series portray the advances of the research in the field of interferometric photonic technology and its novel applications. The wide scope explored by the range of different contributions intends to provide a synopsis of the current research trends and the state of the art in this field, covering recent technological improvements, new production methodologies and emerging applications, for researchers coming from different fields of science and industry. The manuscripts published in the Special issue, and re-printed in this book series, report on topics that range from interferometric sensors for thickness and dynamic displacement measurement, up to pulse wave and spirometry applications.